Systematization of Experience: emotions, actions and knowledge of learning-service performed by students of the Pedagogical University Experimental Libertador - Yarines del Carmen Perdomo de Perez (Universitat Politècnica de València, 2016)
This research experience was intended to systematize the practice of community service  of  fifteen  students  of  the Pedagogical  University  Experimental Libertador  de  Barquisimeto  (UPEL-IPB) Venezuela, in light of the emotions, actions and knowledge of these social actors. The  qualitative  paradigm  is  assumed using  the  phenomenological  method supported  by  the  systematization  of experiences. Four steps were considered for  its  development:  systematic  plan design,  fieldwork  and  reconstruction of  experience,  analysis  and  critical interpretation  of  process  and  results. The scenario focused on the program Overcoming  Environment  Barriers  of the Tamaca community, in the Crespo Municipality of Lara State, Venezuela. The  research  techniques  used  were: observation,  written  primary  sources, in-depth  interviews,  triangulation, and  coding  and  categorization  of information. The results of the inquiry allowed to reveal the emotions of the students before the action, to describe the experiences during the actions and to  interpret  the  knowledge  acquired after the actions. It is concluded that community service generated a profound change and personal growth in the early practitioners.  They  highly  appreciated the  activities  they  had  participated, were aware of the ethical commitment that meant the practice and the need to act within the community in a real and significant way.